2022
DOI: 10.3389/fphar.2022.1050775
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection of Gastrodia elata polyphenols against H2O2-induced PC12 cell cytotoxicity by reducing oxidative stress

Abstract: It has been suggested that oxidative stress (OS) has a role in the development of aging and neurodegenerative disorders. Biological molecules are easily damaged by reactive oxygen species, which can ultimately result in necrotic or apoptotic cell death. Foods containing phytochemicals, such as phenolic compounds, may have potential preventive effects against several diseases, including alzheimer’s disease (AD), according to epidemiological and in vitro research. Gastrodia elata is a well-known homology of medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…It is distributed in the mountain regions of China, Korea, Japan, and India [ 113 ]. In the last few decades, approximately 80 compounds have been isolated and identified from G. elata , including gastrodin, organic acids, phenolics, and sterols [ 114 ], suggesting its complementary role in TCM to treat tetanus, neurasthenia [ 113 ], headache, dizziness [ 115 ], and neurological diseases such as stroke [ 116 ], epilepsy [ 117 ], and vascular dementia [ 118 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is distributed in the mountain regions of China, Korea, Japan, and India [ 113 ]. In the last few decades, approximately 80 compounds have been isolated and identified from G. elata , including gastrodin, organic acids, phenolics, and sterols [ 114 ], suggesting its complementary role in TCM to treat tetanus, neurasthenia [ 113 ], headache, dizziness [ 115 ], and neurological diseases such as stroke [ 116 ], epilepsy [ 117 ], and vascular dementia [ 118 ].…”
Section: Discussionmentioning
confidence: 99%
“…The administration of 5–5000 µg/mL of aqueous extract successfully decreased mATXN3 protein aggregation owing to the upregulation of the peroxisome proliferative activated receptor, gamma, coactivator 1 ( PPARGC1A ) mRNA expression, and its downstream target genes, namely SOD2 and CYCS, along with NFE2L2 mRNA expression and its downstream gene expression, namely HMOX1 , NQO1 , GCLC , and GSTP1 . The protein encoded by PPARGC1A regulates mitochondrial biogenesis and genes of antioxidant response, whereas NFE2L2 promotes the upregulation of ARE-dependent gene expression following oxidative stress [ 114 ]. Further, 50 µg/mL of the aqueous extract, 1 µM of ammonium glycyrrhizinate (AMGZ), and 10 nM of licochalcone A attenuated oxidative stress in HEK-293 cells with inducible ATXN3/Q 75 -GFP expression by increasing the ratio of GSH to GSSG, decreasing the ROS level and caspase-3 activity, and scavenging of free radicals (extract and licochalcone A).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the use of water may have affected the concentration of GR in the extracts. It is expected that the highest content of GR results in better protective effects because pure GR has been reported to ameliorate inflammation in nerves by inhibiting inflammatory cytokines [ 29 ] and Ca 2 + /CaMKII signals [ 30 ] and spinal cord injury via antioxidant and anti-inflammatory effects [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phenolics from dietary or plant sources have been shown to have neuroprotective effects, particularly against AD. The promising medicine food homology plant Gastrodia elata Blume (G. elata) is an excellent example. , Modern chemical analysis and pharmacological studies have shown that the active constituents of G. elata are mainly gastrodin (a phenolic glycoside) and its derivatives. This has stimulated further exploration of the potentially active gastrodin derivatives in G.…”
Section: Introductionmentioning
confidence: 99%